(3aR,8aR)-2,2,6,6-Tetramethyl-4,4,8,8-tetraphenyltetrahydro-1,3-dioxolo[4,5-e][1,3,2]dioxasilepine - Hijji, Yousef M. (International Union of Crystallography, 2008)
The title compound, C(33)H(34)O(4)Si, is a dioxasilepine compound, an effective chiral dopant for the determination of high helical twisting powers in liquid crystals. Its structure consists of a five-membered dioxolo ring fused to a seven-membered dioxasilepine ring which contains two sets of phenyl rings in a twisted butterfly shape attached to the two Csp (3) atoms in the ring opposite each other. Two methyl groups are attached to the Si atom in the ring and two additional methyl groups are attached to the Csp (3) atom in the dioxolo ring (one of which is disordered) and which lies in an envelope pattern. The dihedral angles between the mean planes of the phenyl ring pairs are 85.9 (2) and 83.5 (1)°. The dihedral angles between the mean planes of the dioxolo ring and the two pairs of butterfly shaped phenyl rings are 46.2 (1), 67.7 (1), 35.6 (7) and 83.5 (1)°.